Characterisation and evaluation of pharmaceutical solvates of Atorvastatin calcium by thermoanalytical and spectroscopic studies - Chadha, Renu (BioMed Central, 2012)
BACKGROUND: Atorvastatin calcium (ATC), an anti-lipid biopharmaceutical class II drug, is widely prescribed as a cholesterol-lowering agent and is presently the world’s best-selling medicine. A large number of crystalline forms of ATC have been published in patents. A variety of solid forms may give rise to different physical properties. Therefore, the discovery of new forms of this unusual molecule, ATC, may still provide an opportunity for further improvement of advantageous properties. RESULTS: In the present work, eight new solvates (Solvate I-VIII) have been discovered by recrystallization method. Thermal behaviour of ATC and its solvates studied by DSC and TGA indicate similar pattern suggesting similar mode of entrapment of solvent molecules. The type of solvent present in the crystal lattice of the solvates is identified by GC-MS analysis and the stoichiometric ratio of the solvents is confirmed by (1)HNMR. The high positive value of binding energy determined from thermochemical parameters indicates deep inclusion of the solvent molecules into the host cavity. The XRPD patterns point towards the differences in their crystallanity, however, after desolvation solvate II, III, IV, V and VIII transform to isostructral amorphous desolvated solvates. The order of crystallinity was confirmed by solution calorimetric technique as the enthalpy of solution is an indirect measure of lattice energy. All the solvates behaved endothermically following the order solvate-VIII (1-butanol solvate) < solvate-I (isoproplyate) < solvate-V (methanol solvate) < solvate-III (ethonalate) < solvate-VI (acetone ethanol solvate) < solvate-IV (t-butanol solvate) < solvate-II (THF solvate) < solvate-VII (mixed hemi-ethanol hydrate). The positive value of the heat capacity of the solvate formation provides information about the state of solvent molecules in the host lattice. The solvents molecules incorporated in the crystal lattice induced local chemical environment changes in the drug molecules which are observed in (13)CP/MAS NMR spectral changes. CONCLUSIONS: Aqueous solubility of solvate-VIII was found to be maximum, however, solvate-I and VIII showed better reduction in total cholesterol and triglyceride levels as compared to atorvastatin against triton-induced dyslipidemia.